Performance Analysis of the Village Unit Cooperative (KUD) “Suka Makmur” Using the Balanced Score Card - Herlyna Novasari Siahaan; Mia Wananda Varwasih; Rahmi Nofitasari (Universitas Muhammadiyah Malang, 2024)
This study aims to analyse the performance of the village unit cooperative (KUD) “Suka Makmur” using the Balanced Scorecard instrument because cooperatives must be run with good management by implementing Good Corporate Governance (GCG). Therefore, it is necessary to measure the performance of cooperatives that focus on financial and non-financial performance. This research was conducted from July to October 2023 at the KUD “Suka Makmur”. Mixed methods are used for primary and secondary data. According to the results of research on customer and membership perspectives, it shows that the existing membership at the KUD “Suka Makmur” totals 1,978 people, where the 2021-2022 membership comparison has no cooperative members who have resigned. Second, the financial aspect shows that the results of financial ratios (liquidity, solvency, and profitability) of the KUD “Suka Makmur” are in good condition, the third aspect of the cooperative business is related to the business of buying and selling FFB, UKM Mart, agricultural production facilities unit and savings and loan unit. According to the fourth learning and growth perspective, there are efforts made by cooperatives aimed at improving the ability of cooperative human resources through cooperative training and education, as well as assistance from the Ministry of Cooperatives and the West Tanjung Jabung Cooperative Office.